Diabetic retinopathy screening programme utilising non‐mydriatic fundus imaging in slum populations of New Delhi, India. Issue 4 (1st March 2018) - Wadhwani, Meenakshi; Vashist, Praveen; Singh, Suraj Senjam; Gupta, Noopur; Malhotra, Sumit; Gupta, Aparna; Shukla, Pallavi; Bhardwaj, Amit; Gupta, Vivek
Abstract: Objectives: To develop and implement a community‐based programme for screening of diabetic retinopathy (DR) in urban populations of Delhi. Methods: Known diabetics (KDs) aged 40 years and older were identified through house‐to‐house surveys, volunteers and publicity. All KDs were referred to DR screening camps organised locally where procedures included brief medical history, ocular examination and non‐mydriatic fundus photography using portable handheld camera. Fundal images were graded on the spot by trained optometrists for DR. Patients with DR were referred to tertiary centre for management. Results: A total of 11 566 KDs were identified, of whom 9435 (81.6%) visited DR screening camps and 8432 (89.4%) had DR gradable images. DR was identified in 13.5% of subjects; 351 cases were mild NPDR, 567 moderate, 92 severe. Seventy‐seven had PDR, and 49 had DME, and 2.7% of participants were blind (presenting visual acuity <3/60 in better eye). Non‐use of lifestyle management, presence of systemic complications, BMI <18.5 kg/m 2, disease duration of >5 years and uncontrolled diabetes were associated with increased odds of DR. All cases with DR were referred, and 420 (37%) successful referrals to base hospital were observed. Conclusion: The programme of creating awareness about DR, identifying KDs and optometrist‐led DR screening using non‐mydriatic fundus camera based in slums was successful.